Formation and Development of the European Union Monetary and Financial Mechanism of Anti-Crisis Regulation (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The nature, functions and structure of the monetary and financial mechanism of anti-crisis regulation in the EU are explored. In particular, the role of the European System of Central Banks and the European Commission in this mechanism is analyzed. The formation of a banking union in the EU and its components are also considered, with special attention being paid to the European Stabilization Mechanism. The conditions, stages and consequences of cooperation between the European Stabilization Mechanism and Greece are analyzed. The International Monetary Fund’s assessment of the austerity measures applied by the European Stabilization Mechanism for Greece and other countries is presented.
Keywords: international monetary and financial relations, global financial and economic crisis, European Union, Eurozone, anti-crisis regulation.